A Klebsiella pneumoniae bacteriophage and its effect on 1, 3-propanediol fermentation. Issue 10 (October 2016) - Shen, Juntao; Zhou, Jinjie; Fu, Hongxin; Mu, Ying; Sun, Yaqin; Xu, Yongping; Xiu, Zhilong
Graphical abstract: Highlights: A phage specially infecting Klebsiella pneumoniae was characterized. Different sluggish fermentations depending on the infection time were observed. Fermentation failed to recover for phage infection at the exponential phase. Cell densities increased 25.8% for phage infection at initial time. Abstract: Bacteriophage infection is one of potential threats in bacterial fermentations. In the present study, a phage specially infecting Klebsiella pneumoniae was characterized and its effect on 1, 3-propanediol fermentation was investigated. It belongs to the Siphoviridae family with an icosahedral head of 64 ± 2 nm in diameter and a long tail of 158 ± 3 nm and has a double-stranded DNA of about 45 kbp. The infection kinetics and stability of phage phiKpS2 were also determined. Then, phage infection at different growth phases were carried out in laboratory to evaluate its impact for PDO production. Different sluggish fermentations depending on the infection time at different cell growth phases were observed. Fermentation failed to recover even adding new medium when phage infected at 4 h in fed-batch fermentation. However, the maximum biomass increased 25.8% after about 8 h of lag time when phage infected at 0 h, which led to the increase of PDO production from 69.7 ± 2.1 g/L to 85.2 ± 0.8 g/L. In addition, pH fluctuations were also observed along with cells lysis and growth recovery.